Experimental Validation of Numerical Model for Bi-Tilt-Isolator - Ming-Hsiang Shih; Wen-Pei Sung; Chia-Yu Ho (Shock and Vibration)
Bi-Tilt Isolator (BTI) is composed of bi-tilt beveled substrate and slider. The advantages of BTI are that the maximum upload seismic force of structure can be easily controlled and displacement of isolation layer will be reduced. Sliding force, friction force, and impulse force are caused in the slanting process of BTI, nonlinear behavior. A nonlinear mathematical model is derived based on the sliding upwards, sliding downwards, and transition stages. Then, BTI element of nonlinear analysis program, GENDYN, is developed by the fourth-order Runge-Kutta method, the discretized ordinary differential equation for three movement stages of BTI. Then, test set-up of superstructure installed with BTI is tested and recorded the real displacement and acceleration responses under conditions of full lubrication, mild lubrication, and without lubrication between interface of bi-tilt beveled substrate and slider with three various initial displacements. The comparison of simulation results and test results shows the following: (1) root mean square error is below 1.35% for WD40 sprayed, 0.47% for WD40 whipped, and 0.54% for without lubrication, respectively; (2) the maximum root mean square error for simulating with cubic polynomial function of friction is much less than those of constant friction except conditions of full lubrication, which are not affected by kinetic friction force; (3) application of cubic polynomial function for simulating friction of BTI with three different lubricated conditions can perform very fine simulation results, compared with the test results. This proposed mathematical model and BTI element of GENDYN program, using cubic polynomial function of friction, perform fine simulation capability to assess nonlinear isolation effect of structure installed with BTI.